Unit Commitment with Renewable Energy Using Multi-agent Immune System Incorporating Evolutionary Priority List for Operation Cost Minimization (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Renewable energy (RE) integration into the power grid is steadily growing that effectively reducing the electricity generation cost, however, leads to additional consequences. Unit commitment (UC) problem often cited in discussing these issues. This paper proposes an approach to look at these issues by utilizing the Multi-agent Immune incorporating Evolutionary Priority List (MAI-EPL) technique for solving the UC problem with the consideration of RE resources, as an effort to reduce the operation cost without affecting the existing power system reliability. The employed test systems consider 10 thermal generating units with additional solar and wind resources in a 24-hours scheduling period. The results show that the MAI-EPL technique is capable of producing a satisfactory outcome to the UC problem with RE consideration.